Modification of a Gene Cassette to Express Proglargine in Pichia pastoris: Elimination of Glu-Ala Repeats, Spacer and C-peptide Sequences - Nasution, Uli Julia; Astuti, Rika Indri; Wahyudi, Aris Tri; Hardianto, Dudi; Martius, Efrida (Journal of Multidisciplinary Applied Natural Science, 2026)
The growing global prevalence of diabetes mellitus has sharply increased the demand for insulin and its analogues. Pichia pastoris is a well-established system for recombinant pro-insulin and its analogues production. However, conventional gene constructs often include additional sequences, such as Glu-Ala repeats, spacer peptides, and c-peptides that complicate downstream processing and reduce efficiency. This study aimed to construct and express a proglargine (PG) gene cassette lacking the Glu-Ala repeats, spacer, and c-peptide in P. pastoris GS115 to obtain a uniform PG protein. The recombinant vector propagated in Escherichia coli TOP10F’, then expressed in P. pastorisGS115. Selected transformants were cultivated in YPG medium, then induced with 1% and 2% methanol daily in BMMY. The optimum methanol concentration further evaluated in ½ BSM induction medium. The result demonstrated that optimal PG expression was achieved with 2% methanol induction in BMMY, producing higher levels than those with ½ BSM. Among the transformants, PG.c2 produced the highest PG protein in BMMY medium induced with 2% methanol. Dot-blot analysis confirmed the secretion of PG, and LC-HRMS analysis demonstrated 100% amino acid sequence coverage of PG, confirming the integrity and completeness of the expressed protein. This study presented a newly modified PG gene cassette, inserted into pPICZαA vector, to express uniform secreted PG in P. pastoris GS115. By simplifying the precursor structure, a more homogeneous precursor product can be obtained, which is expected to simplify purification and also the downstream enzymatic process of PG into mature insulin glargine.